Market development and food demand in rural China - Huang, Jikun; Rozelle, Scott (International Food Policy Research Institute, 1995)
This paper seeks to understand how market imperfections affect the behavior of consumers in China's rural economy. A theoretical and empirical model is developed and estimated using a household-level data from six counties in Hebei Province. The results show that market development plays an important role in explaining food consumption behavior in China. As the market develops, farmers demand less grain and vegetables and consume more meat, fruit, and other food products after control for income and price effects. Moreover, the elasticities of demand also change as farm households begin to rely more on rural markets. The results of this paper suggest that a government concerned about the welfare of its rural population may want to be paying a more active role in fostering rural markets. Understanding the forces behind these consumption pattern shifts also will aid academics and policymakers in making better projections about future consumerneeds and price levels.